Gene expression and enzyme activities of carbonic anhydrase and glutaminase in rat kidneys induced by chronic systemic hypoxia (Medical Journal of Indonesia, 2015)
Background: Hypoxia can cause acidosis. Kidney plays an essential role in maintaining acid-base balance, which involves the activities of carbonic anhydrase (CA) and glutaminase (GLS). This study is aimed to determine the expression and activities of the CA9 and GLS1 enzymes in relation to hypoxia inducible factor-1α (HIF-1α), a transcription factor protein which is a marker of hypoxia. Methods: This study was an in vivo experimental study with coupled paralel design. used 25 male Sprague-Dawley rats weighing 150-200 g. Rats were divided into 5 groups: the control group (normoxic condition) and 4 treatment groups. The latter were kept in a hypoxic chamber (10% O2: 90% N2) for 1, 3, 5 and 7 days. All rats were euthanized after treatment, kidneys excised, tissues homogenized and investigated for gene expression of CA9, GLS1 and HIF-1α. On protein level, total enzymatic activities of CA and GLS and protein of HIF-1α were also investigated. Data were analyzed statistically using ANOVA for significance, and as its alternative, used Mann-Whitney and Kruskal-Wallis test. Results: Results showed that HIF-1α mRNA increased during hypoxia, but not HIF-1α protein. It seemed that acidosis occurs in kidney tissue, indicated by increased CA9 and GLS1 mRNA expression and specific activity of total CA and GLS1. Expression of CA9 and GLS1 mRNA both showed strong positive correlation with HIF-1α mRNA, but not with HIF-1α protein. Conclusion: It is suggested that during chronic systemic hypoxia, gene expression of CA9 and GLS1 and their enzyme activities were increased as a response to acidosis and related with the expression of HIF-1α mRNA.